Mating behavior of Patagonian octopus (Octopus tehuelchus) under laboratory conditions - Berrueta, Maria Mercedes (2020)
Patagonian octopus (Octopus tehuelchus) is a species that holds an artisanal fishery in the northern area of the Argentine Patagonian coast and has a potential for aquaculture development. This work aimed to characterize the mating behavior of four pairs of Patagonian octopuses under laboratory conditions. Results showed that this species has a complex reproductive behavior. Female remained in her shelter during pre-copulation and copulation events. Male and female remained faced by the oral face during sexual intercourse, which lasted 3 to 5 min. Remarkably, female patagonian octopus remains inside his shelter during pre-copulation and intercourse events. The observations will contribute to the better management of the reproductive specimens of the species in captivity.